Temporal changes of tibial eminence after bi-cruciate retaining total knee arthroplasty - Hiroshi Inui; Ryota Yamagami; Kenichi Kono; Kohei Kawaguchi; Kazuo Saita; Shuji Taketomi; Sakae Tanaka (BMC Musculoskeletal Disorders, 2025)
Abstract Background Bicruciate-retaining (BCR) prostheses have been introduced to recreate normal knee movements by preserving both the anterior and posterior cruciate ligaments. One of the surgical procedures essential to the success of BCR total knee arthroplasty (TKA) is preservation of the tibial eminence. However, in our clinical experience, we found that a well-preserved tibial eminence changed its shape chronologically after the operation. This study aimed to investigate the frequency of chronological changes in the tibial eminence after BCR TKA and its influence on the outcomes. Methods This study included 59 patients with BCR TKA. Radiographs taken at 2 weeks postoperatively and at an average follow-up of 3.2 years were used to assess the tibial eminence. The patients’ demographics, joint component gaps, and clinical scores were compared between the groups with chronological change (P group) and without change (N group). Results The chronological change of the tibial eminence was found in 22 cases (37%). The joint component gaps at extension were larger in P group than in N group. The scores in the symptoms and ADL subscales of the KOOS were significantly higher at 1 year postoperatively in N group than in P group. There were no significant differences between the two groups at the final follow-up. Conclusions Chronological changes in the well-preserved tibial eminence were found in approximately one third of the BCR TKA patients. The mean scores at 1-year postoperatively were lower in the patients with chronological changes in the tibial eminence than in the patients without changes.